A method for reducing the contact resistance of flexible graphite composite bipolar plates and quickly adjusting the thickness
By pressing the expanded graphite roller into low-density prefabricated plates of different thicknesses, and dilute resin impregnation and surface treatment, four types of prefabricated plates were prepared, which solved the problem of high contact resistance and discontinuous thickness adjustment of flexible graphite composite bipolar plates. Achieve efficient and environmentally friendly bipolar plate production.
Patent Information
- Application Number
- CN202411499128.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing flexible graphite composite bipolar plates need to be cleaned off the resin attached to the surface to reduce the contact resistance before curing and forming. This process consumes a large amount of solvent and is not environmentally friendly. In addition, the adjustment method of the plate thickness is discontinuous, which affects production efficiency.
Four kinds of prefabricated plates were obtained by pressing the expanded graphite roller into low-density prefabricated plates of different thicknesses and vacuum impregnating with dilute resin. These prefabricated plates can be combined and stacked according to product design requirements and hot-pressed to prepare bipolar plates of any thickness.
It has achieved the reduction of the contact resistance of the flexible graphite composite bipolar plate, and the thickness is quickly adjusted through four specifications of prefabricated plates. The process is simple and environmentally friendly, suitable for mass production, and has high conductivity and low contact resistance.
Smart Images

Figure CN119050395B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for reducing the contact resistance of a flexible graphite composite bipolar plate and quickly adjusting the thickness, and belongs to the technical field of proton exchange membrane fuel cell materials. Background Art
[0002] The proton exchange membrane fuel cell (PEMFC) is mainly composed of a proton exchange membrane, a catalyst layer, a gas diffusion layer and a bipolar plate. The two sides of the bipolar plate are in contact with the membrane electrodes of the anode and cathode respectively, playing many important roles such as supporting the membrane electrode structure, separating hydrogen and oxygen, providing channels, collecting electrons, conducting heat, discharging water generated by the reaction, and providing coolant flow channels. Generally speaking, the bipolar plate accounts for more than 70% of the total mass of the stack and about 30% of the total cost. The preparation of composite bipolar plates based on graphite and resin materials is currently a more mainstream method, which has good electrical conductivity, thermal conductivity, corrosion resistance and mechanical strength. However, since the resin itself is not conductive, the plate needs to be cleaned of the resin attached to the surface before curing to reduce the contact resistance. This process consumes a lot of solvents and is not environmentally friendly. In addition, in order to meet the technical requirements of various fuel cell stacks, the thickness of the plate also needs to be adjusted frequently, and the current adjustment method only changes the thickness of the prefabricated plate, resulting in discontinuity in the process and affecting production efficiency.
[0003] Therefore, developing environmentally friendly and efficient surface treatment processes for flexible graphite composite bipolar plates and methods for quickly adjusting thickness can bring significant gains to plate processing. Summary of the invention
[0004] The present invention first rolls expanded graphite into two low-density prefabricated plates of different thicknesses, then vacuum impregnates with dilute resin, performs surface treatment on one side of some prefabricated plates of the two thicknesses and dries them as outer prefabricated plates, and dries the remaining prefabricated plates as inner prefabricated plates, thereby obtaining four types of prefabricated plates, which are then stacked and hot-pressed according to product design requirements. Bipolar plates of any thickness can be prepared using only these four types of prefabricated plates.
[0005] The purpose of the present invention is to provide a method for reducing the contact resistance of a flexible graphite composite bipolar plate and quickly adjusting the thickness. The flexible graphite composite bipolar plate is firstly formed into a low-density prefabricated plate by cold pressing of expanded graphite, and then vacuum impregnated with a dilute resin. A single side of a part of the prefabricated plate is surface treated and dried as an outer prefabricated plate, and the remaining is dried as an inner prefabricated plate. Finally, the flexible graphite composite bipolar plate is stacked and hot-pressed according to the product thickness requirements.
[0006] The flexible graphite composite bipolar plate is molded from at least two layers of prefabricated plates, and the minimum thickness of the flexible graphite composite bipolar plate is 0.3 mm; the outermost layers of the flexible graphite composite bipolar plate are respectively outer prefabricated plates on both sides, and the side after surface treatment faces outward. When the flexible graphite composite bipolar plate has three layers or more, the middle layer is the inner prefabricated plate;
[0007] The density of the flexible graphite composite bipolar plate is 1.5-1.8 g / cm 3 ;
[0008] The electrical conductivity of the flexible graphite composite bipolar plate is 300-400 S / cm.
[0009] The contact resistance of the flexible graphite composite bipolar plate is ≤3.0 mΩ*cm 2 .
[0010] Furthermore, in the above technical solution, the low-density prefabricated panels have at least two thicknesses.
[0011] Furthermore, in the above technical solution, the solution includes the following steps:
[0012] (1) preforming the expanded graphite worms by roller pressing to obtain a plurality of low-density prefabricated plates;
[0013] (2) placing the low-density prefabricated board obtained in the previous step in a dilute resin impregnation liquid for vacuum impregnation to obtain a wet board, performing single-side surface treatment on a portion of the wet board and then drying it as an outer layer prefabricated board, and directly drying the other portion as an inner layer prefabricated board;
[0014] (3) According to product design requirements, the prefabricated plates obtained in the previous step are stacked and combined to adjust the total thickness before molding, and are placed in a mold for hot pressing to obtain a flexible graphite composite bipolar plate with a flow field.
[0015] Furthermore, in the above technical solution, in step (1), the bulk density of the expanded graphite worms is 0.004-0.008 g / cm 3 The thickness of the plurality of low-density prefabricated panels is the same or different, and the thickness is selected from 1-10 mm, preferably 2 mm and 3 mm, and the density of the low-density prefabricated panels is 0.075-0.125 g / cm 3 .
[0016] Furthermore, in the above technical solution, in step (2), the resin component of the dilute resin impregnation solution is: one or a mixture of phenolic resin, epoxy resin, vinyl ester resin, polyvinylidene fluoride resin, and acrylic resin.
[0017] The dilute resin impregnation liquid has a solid content of 1-10% and can be in the form of an emulsion or a solution. The solvent used to dilute the resin is one or a mixture of deionized water, methanol, ethanol, acetone, butanone, toluene, xylene, styrene, ethyl acetate, dibasic acid ester, N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl sulfoxide.
[0018] The vacuum degree of the vacuum impregnation is -0.08 to -0.1 MPa, and the impregnation time is 4 to 6 hours.
[0019] Furthermore, in the above technical solution, in step (2), the surface treatment method is to dry-spray the conductive agent powder on the outer side of the outer prefabricated plate, that is, the side in contact with the membrane electrode, and the conductive agent used is one or a mixture of expanded graphite powder, graphene, and carbon nanotubes with a mesh size of more than 100. The coating thickness of the powder spraying is 10-20 μm, and the surface density is 1.5-3.5 mg / cm 2 It should be noted that a layer of resin impregnation liquid remains on the surface of the wet prefabricated board before drying, and the conductive agent will directly adhere to the surface after powder spraying and will not fall off easily after drying.
[0020] Furthermore, in the above technical solution, the drying temperature is 60-120° C., the drying time is 4-8 h, and the inner layer board and the outer layer board adopt the same drying temperature and time.
[0021] Furthermore, in the above technical solution, there are four types of prefabricated panels, namely, 2mm inner prefabricated panels, 3mm inner prefabricated panels, 2mm outer prefabricated panels, and 3mm outer prefabricated panels. Figure 1 As shown, both have been dried. The two outer panels are divided into inner and outer surfaces. The outer surfaces are powder-coated and can be distinguished by appearance.
[0022] Furthermore, in the above technical solution, in step (3), the total thickness of the prefabricated board before molding is adjusted, and the adjustment range is 4mm at the lowest and the minimum adjustment amplitude is 1mm. The adjustment method is, for example: if the total thickness before molding is 5mm, the stacking order is 2mm outer layer board + 3mm outer layer board, such as Figure 2 As shown; the total thickness before molding is 7mm, so the stacking order is 2mm outer layer board + 3mm inner layer board + 2mm outer layer board, such as Figure 3 As shown; the total thickness before molding is 8mm, so the stacking order is 3mm outer layer board + 2mm inner layer board + 3mm outer layer board, such as Figure 4 As shown. It should be noted that the surface treatment layers are facing outwards when stacked. For the thickness after molding, the minimum adjustment range is no more than 0.1mm, which will vary depending on the selection and content of the prefabricated board resin and the molding process conditions.
[0023] Furthermore, in the above technical solution, in step (3), the temperature of the hot pressing molding is 150-200° C., the pressure is 8-16 MPa, and the curing time is 3-120 min.
[0024] The advantages of this application are:
[0025] The present invention proposes a method for reducing the contact resistance of flexible graphite composite bipolar plates and quickly adjusting the thickness. The process is simple and environmentally friendly. Plates of various thicknesses can be prepared by using only four prefabricated plates with extremely high conductivity and extremely low contact resistance. The present invention is suitable for mass production in workshops. The process is divided into a completely decoupled wet section and a dry section. The products obtained in the wet section (i.e., four prefabricated plates) can be directly molded or roll-formed without any treatment, so they can be sold as commodities, greatly shortening the production cycle of upstream enterprises and reducing the cost pressure caused by mold opening. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the structure of the inner plate and the outer plate;
[0027] Figure 2 This is a schematic diagram of the structure of the stacked prefabricated panels, with a total thickness of 5mm before molding;
[0028] Figure 3 This is a schematic diagram of the structure of the stacked prefabricated panels, with a total thickness of 7mm before molding;
[0029] Figure 4 This is a schematic diagram of the stacked prefabricated panel structure, with a total thickness of 8mm before molding. DETAILED DESCRIPTION
[0030] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0031] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0032] Example 1
[0033] A flexible graphite prefabricated plate assembly is prepared according to the following steps:
[0034] (1) The expanded graphite worms were preformed by rolling to a density of 0.1 g / cm 3 , thickness 2mm and density 0.1g / cm 3 , Plate with thickness of 3mm;
[0035] (2) Phenolic 2123 resin was added to ethanol to prepare an impregnation solution with a solid content of 7.5%. The two boards obtained in the previous step were placed in the impregnation solution for vacuum impregnation. The boards were allowed to stand for 2 h at a vacuum degree of -0.08±0.01 MPa. After the boards were sunk below the surface of the impregnation solution, the pressure was restored to normal. After standing for another 2 h, the boards were drained and taken out. A portion of the 2 mm and 3 mm thick boards were directly dried at a drying temperature of 85 °C for 4 h to obtain 2 mm inner layer boards and 3 mm inner layer boards ( Figure 1 );
[0036] (3) Multi-walled graphene and 325 mesh expanded graphite powder were uniformly mixed in a ratio of 1:20, and the mixed powder was sprayed on one side of another portion of 2 mm and 3 mm thick plates obtained after the impregnation in step (2), and the spraying amount was controlled to be 2 ± 0.2 mg / cm 2 After spraying, drying was performed at 85°C for 4 hours to obtain 2 mm outer layer boards and 3 mm outer layer boards ( Figure 1 );
[0037] (4) The four impregnated prefabricated panels obtained in step (2) and step (3) are stacked together with the sprayed side facing outward. The thickness of the combined panels can be quickly adjusted in 1 mm increments to suit the molding process (see Figure 2 , Figure 3 , Figure 4 The molding process parameters are as follows: the pressure is maintained at 165°C and 30MPa for 10 minutes, then cooled to room temperature and the mold is opened for sampling. The thickness of the 5mm prefabricated board after molding is 0.38mm; the thickness of the 7mm prefabricated board after molding is 0.54mm; and the thickness of the 8mm prefabricated board after molding is 0.6mm.
[0038] Example 2
[0039] A flexible graphite composite bipolar plate is prepared according to the following steps:
[0040] (1) Prepare a 3 mm outer layer plate and a 2 mm inner layer plate according to the method described in Example 1. Figure 4 The stacking sequence shown is combined into a prefabricated panel with a total thickness of 8 mm;
[0041] (2) Add 5.0 g of polyvinylidene fluoride resin to 195 g of N-methylpyrrolidone solvent oil to prepare a 200 g solution, and stir at 60° C. for 4 h to obtain a dilute resin impregnation solution;
[0042] (3) Inject the dilute resin impregnation liquid obtained in step (2) into a small flat-bottomed tray with a liquid level of 16 mm (not less than 2 times the total thickness of the prefabricated board of 8 mm). Gently place the prefabricated board obtained in step (1) on the surface of the impregnation liquid. The prefabricated board should be floating at this time. Place the tray containing the impregnation liquid and the prefabricated board in a vacuum oven and evacuate the tray. Maintain the vacuum degree at -0.08~-0.1MPa. After immersion for 4 hours, restore the pressure to normal and take out the tray. At this time, the prefabricated board sinks to the bottom layer of the impregnation liquid. Take out the prefabricated board, rinse off the residual resin on the surface with a solvent (D60 solvent oil or ethyl acetate), and then place it in an oven with exhaust gas treatment to dry the solvent. The drying temperature is 120°C and the drying time is 4 hours. After drying, the impregnated prefabricated board is obtained;
[0043] (4) Use a die cutter to cut the prefabricated plate obtained in the previous step and place it in a mold for hot pressing. Keep it at 160°C and 15MPa for 10 minutes and then stop heating. After the mold cools to below 80°C, release the pressure and open the mold to obtain the finished bipolar plate. The total thickness of the bipolar plate is 1.1mm, the thinnest part is 0.3mm, the conductivity is 370S / cm, and the contact resistance of the diffusion layer is 2.7mΩ*cm 2 .
[0044] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for reducing the contact resistance of a flexible graphite composite bipolar plate and quickly adjusting the thickness, characterized in that: The flexible graphite composite bipolar plate is firstly formed into a low-density prefabricated plate by cold pressing expanded graphite, and then vacuum impregnated with a dilute resin, and a single side of some prefabricated plates is surface treated and dried as an outer prefabricated plate, and the remaining prefabricated plates are dried as inner prefabricated plates, and finally combined and stacked according to product thickness requirements and hot-pressed to form the plate; The flexible graphite composite bipolar plate is molded from at least two layers of prefabricated plates, and the minimum thickness of the flexible graphite composite bipolar plate is 0.3 mm; the outermost layers of the flexible graphite composite bipolar plate are respectively outer prefabricated plates on both sides, and the side after surface treatment faces outward. When the flexible graphite composite bipolar plate has three layers or more, the middle layer is the inner prefabricated plate; The density of the flexible graphite composite bipolar plate is 1.5-1.8 g / cm 3 ; The electrical conductivity of the flexible graphite composite bipolar plate is 300-400 S / cm; The contact resistance of the flexible graphite composite bipolar plate is ≤3.0 mΩ*cm 2 ; The low-density prefabricated panels have at least two thicknesses; The surface treatment method comprises the following steps: dry spraying the conductive agent powder on the outer side of the outer prefabricated plate, i.e., the side in contact with the membrane electrode, wherein the conductive agent used is one or a mixture of expanded graphite powder, graphene, and carbon nanotubes with a mesh size of more than 100; the coating thickness of the powder spraying is 10-20 μm, and the surface density is 1.5-3.5 mg / cm 2 .
2. The method according to claim 1, characterized in that The following steps are involved: (1) preforming the expanded graphite worms by roller pressing to obtain a plurality of low-density prefabricated plates; (2) placing the low-density prefabricated board obtained in the previous step in a dilute resin impregnation liquid for vacuum impregnation to obtain a wet board, performing single-side surface treatment on a portion of the wet board and then drying it as an outer layer prefabricated board, and directly drying the other portion as an inner layer prefabricated board; (3) According to product design requirements, the prefabricated plates obtained in the previous step are stacked and combined to adjust the total thickness before molding, and are placed in a mold for hot pressing to obtain a flexible graphite composite bipolar plate with a flow field.
3. The method according to claim 2, characterized in that In step (1), the bulk density of the expanded graphite worms is 0.004-0.008 g / cm 3 The thickness of the plurality of low-density prefabricated panels is the same or different, and the thickness is selected from 1-10 mm. The density of the low-density prefabricated panels is 0.075-0.125 g / cm 3 .
4. The method according to claim 2, characterized in that: In step (2), the resin component of the dilute resin impregnation solution is: one or a mixture of phenolic resin, epoxy resin, vinyl ester resin, polyvinylidene fluoride resin, acrylic resin; The dilute resin impregnation liquid has a solid content of 1-10% and can be in the form of an emulsion or a solution. The solvent used to dilute the resin is one or a mixture of deionized water, methanol, ethanol, acetone, butanone, toluene, xylene, styrene, ethyl acetate, dibasic acid ester, N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl sulfoxide; The vacuum degree of the vacuum impregnation is -0.08 to -0.1 MPa, and the impregnation time is 4 to 6 hours.
5. The method according to claim 2, characterized in that: The drying temperature is 60-120° C., the drying time is 4-8 hours, and the inner and outer layers are dried in the same manner.
6. The method according to claim 2, characterized in that There are four types of prefabricated panels, namely, 2mm inner layer prefabricated panels, 3mm inner layer prefabricated panels, 2mm outer layer prefabricated panels, and 3mm outer layer prefabricated panels.
7. The method according to claim 2, characterized in that: In step (3), the total thickness of the prefabricated board before molding is adjusted, and the adjustment range is a minimum of 4 mm, and the minimum adjustment amplitude is 1 mm.
8. The method according to claim 2, characterized in that: In step (3), the temperature of the hot pressing molding is 150-200° C., the pressure is 8-16 MPa, and the curing time is 3-120 min.
Citation Information
Patent Citations
Expansion graphite base compound material dual-pole board and its making method
CN101101994A
Preparation method of conductive polymer-graphene composite bipolar plate
CN108199058A